Comparison of Intravenous Paracetamol and Tramadol for Postoperative Analgesia in Patients Undergoing Open Appendectomy: A Prospective Comparative Study - Chetan Bohara,; Parshal Bhandari,; Bandana Kafle,; Khagendra Gautam,; Gunjan Regmi,; Prashanna Bajracharya, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Effective postoperative pain management after open appendectomy is crucial to minimize complications and support recovery. Intravenous (IV) paracetamol offers safe, well-tolerated pain control, and tramadol offers effective analgesia but accompanied with opioids related side effects. So, effectiveness and safety of IV paracetamol and tramadol for postoperative analgesia after open appendectomy were compared in this study.Materials and Methods: A comparative cohort study was conducted at Lumbini medical college & teaching hospital, Nepal, involving 110 patients (aged 18–60 years, ASA I or II) who were scheduled for open appendectomy. Appendectomy was done under spinal anaesthesia for all cases. Upon completion of the surgery, patients were immediately shifted to the post-anaesthesia care unit (PACU). Patients were divided into two cohorts: Group P (n=55) received intravenous paracetamol and Group T (n=55) received intravenous tramadol every 6 hours for 24 hours. Pain intensity was assessed using the Visual Analogue Scale (VAS) at baseline 0, 30 minutes, 2, 6, 12, 18, and 24 hours after giving first dose of analgesia. Ketorolac was given as rescue analgesia if VAS ≥ 4. Adverse effects (nausea, vomiting, dizziness) and additional analgesic requirements were recorded. Data was analyzed using Student’s t-test and chi-square test, with p < 0.05 considered significant.Results: Demographic and clinical characteristics were comparable between groups (p > 0.05). At 30 minutes post-PACU, Group P had significantly higher VAS scores (1.29 ± 1.44) compared to Group T (0.73 ± 1.06; p = 0.021). No significant differences in VAS scores were observed at other time points over 24 hours (p > 0.05). The 24-hour cumulative rescue ketorolac dose was similar between groups (p = 0.411). Nausea (p = 0.017) and vomiting (p = 0.031) were significantly higher in Group T, while dizziness incidence was comparable (p = 0.112).Conclusion: Both paracetamol and tramadol provided adequate post operative analgesia after open appendectomy with low incidence of side effects with paracetamol analgesia.